2012
DOI: 10.2224/sbp.2012.40.3.395
|View full text |Cite
|
Sign up to set email alerts
|

The Empathy-Altruism Association and Its Relevance to Health Care Professions

Abstract: It is posited in the empathy-altruism hypothesis that altruistic motivation evoked by empathy is directed toward the ultimate goal of improving another person's welfare. In this study the empathy-altruism hypothesis was examined. Measures of altruism, empathy, and social desirability were completed by 112 individuals in a university setting. A positive and significant association was found between altruism and empathy (r^ = .24, p = .01, 95% CI [.06-.41]). No significant associations were found between social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 8 publications
2
32
0
2
Order By: Relevance
“…This finding is consistent with the empathy–altruism hypothesis (Batson, ) and Eisenberg et al's () assertion that greater perspective‐taking ability increases empathic concern and altruistic behavior. Our findings also align with Burks et al's () study, which found a significant relationship between empathy and altruism among health care professionals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with the empathy–altruism hypothesis (Batson, ) and Eisenberg et al's () assertion that greater perspective‐taking ability increases empathic concern and altruistic behavior. Our findings also align with Burks et al's () study, which found a significant relationship between empathy and altruism among health care professionals.…”
Section: Discussionsupporting
confidence: 92%
“…Another aspect of the cognitive factor is the notion that individuals who have greater perspective‐taking ability also have higher levels of empathic concern, which increases altruistic behavior (Eisenberg, Miller, Shell, McNalley, & Shea, ). For example, Burks, Youll, and Durtschi () found a significant relationship between empathy and altruism among health care professionals.…”
mentioning
confidence: 99%
“…The social psychology literature defines altruism as “a motivational state, altruism sometimes propagates prosocial, helping, or altruistic behaviors, that focus on the welfare of other people” (Burks, Youll, & Durtschi, , p. 395). The role of altruism and empathy as applicable to the helping professions has examined the relationship between reduced altruism/empathy and decreased quality of care (Batson, ).…”
Section: Thematic Categoriesmentioning
confidence: 99%
“…Support for the empathy–altruism hypothesis has implications for being responsive to an area of social concern. Burks et al () stated that it is imperative that trainees and helping professionals sustain empathy in their motivations to help others. They encourage those who develop training program curricula to consider empathy in the provision of quality care.…”
Section: Thematic Categoriesmentioning
confidence: 99%
“…People have the general tendencyto feel empathy towards other individuals and a desire to increase their happiness (Batson, 1991;Burks, Youll, & Durtschi, 2012).When that individual belongs to an outgroup; however, empathetic responses can be diminished. In some extreme situations, people even derive pleasure from the suffering of an outgroup member (Cikara, Bruneau & Saxe, 2011;Smith, Powell, Combs, & Schurtz, 2009).…”
Section: Introductionmentioning
confidence: 99%